Pengaruh Implementasi Sistem Informasi Akuntansi (SIA) Dan Sistem Pengendalian Internal (SPI) Terhadap Efisiensi Pengelolaan Penerimaan Negara Bukan Pajak (PNBP) Pada Kejaksaan Negeri Wilayah Sumatera Barat - Delsi Delsi; Sri Asyrafil Mustaqmah (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
This study aims to analyse the effect of the Accounting Information System (AIS) and Internal Control System (ICS) on the efficiency of Non-Tax State Revenue (PNBP) at the District Attorney's Offices in West Sumatra. The research objects include the Bukittinggi District Attorney's Office, the Agam District Attorney's Office, and the Tanah Datar District Attorney's Office. Efficient management of PNBP is an important aspect of achieving transparent, accountable, and effective state financial governance. Therefore, the implementation of a reliable accounting information system and a strong internal control system is essential to support the optimisation of PNBP management. This study employed a quantitative research method with a survey approach. Data were collected through questionnaires distributed to 30 respondents who were directly involved in PNBP management at the three District Attorney's Offices. The data were analysed using the Structural Equation Modelling–Partial Least Squares (SEM-PLS) method with SmartPLS software. The results indicate that both the Accounting Information System and the Internal Control System have a positive and significant effect on the efficiency of PNBP. The findings also reveal that the Internal Control System has a more dominant influence than the Accounting Information System in improving the efficiency of PNBP management. Based on the findings, it can be concluded that the implementation of an effective Accounting Information System, supported by a strong Internal Control System, contributes to improving the efficiency of PNBP management at the District Attorney's Offices in West Sumatra.